2015
DOI: 10.1590/2317-1782/20152013065
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and social competency profiles of stutterers

Abstract: PURPOSE: To investigate the behavioral and social competency profiles of individuals who stutter and to compare them with persons who do not stutter, according to their parents; to correlate the behavioral and the social competence performances with the severity of stuttering. METHODS: Sixty-four participants, aged 6 to 18 years, of both genders, were divided into two groups: the study group (SG), composed of 32 individuals with persistent developmental stuttering, and the control group (CG), composed of 32 fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
0
10
1
2
Order By: Relevance
“…Tendo em vista os resultados obtidos, os dados indicaram que os escolares que gaguejam, ademais de todos os impactos na comunicação e na participação nas atividades de vida diária e em contextos sociais (1,6,7) comumente apresentam impactos nas áreas educacionais (30) , como por exemplo na compreensão de leitura.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Tendo em vista os resultados obtidos, os dados indicaram que os escolares que gaguejam, ademais de todos os impactos na comunicação e na participação nas atividades de vida diária e em contextos sociais (1,6,7) comumente apresentam impactos nas áreas educacionais (30) , como por exemplo na compreensão de leitura.…”
Section: Discussionunclassified
“…Portanto, eles podem deixar de falar ou diminuir sua participação em contextos sociais (6) . Outros pesquisadores também relataram que prejuízos no domínio social e nas situações comunicacionais rotineiras caracterizaram a competência social dos indivíduos com gagueira (7) .…”
Section: Introductionunclassified
“…The questionnaire was divided into five factors for conceptual validity and in these subscales a defined median of r was detected as .81. Mean ± SD/Percentage Age 1 10.5 ± 3.5 11.0 ± 3.6 t = .39, df = 44, p = 0.69 Gender 2 18 (75%, male) 12 ( 54.5%, male) x 2 = 2.1, df = 1, p = 0.12 Maternal education 1 9.1 ± 3.3 11.9 ± 4.1 t = 2.51, df = 44, p = 0.01 Paternal education 1 10. . The responses are given on a four-point scale, ranging from 'I find it not appropriate at all' to 'I find it quite appropriate' , and the total score equals the sum of he 60-items.…”
Section: Parental Attitude Research Instrument (Pari)mentioning
confidence: 99%
“…Developmental stuttering (DS) is a speech disorder with different manifestations, mainly characterized by involuntary repetitions of syllables, blocks, and prolongations, as well as physiological, behavioral, and emotional reactions to the speech disruptions 1,2 . The onset of DS typically occurs between 2 and 4 years of age 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Stutterers usually react to their disfluency by denial, guilt, shame, anxiety, depression, and anger. Their parents reported that they typically have behavioral problems with them and with school peers [14] . Anxiety in stutterers may increase over time till it became more evident in adolescents.…”
Section: Introductionmentioning
confidence: 99%